Sequential Equilibria and Cheap Talk in Infinite Signaling Games - Karl Iorio; Alejandro M. Manuelli (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1990)
This paper shows the existence of sequential and weak-best-response equilibria for cheap-talk extensions of signaling games for a class of signaling games called communication-impervious. An example shows there are well-behaved infinite signaling games with no sequential equilibria. The assumption that talk is cheap seems reasonable in many economic contexts and yields a very straightforward solution to the existence problem in infinite signaling games. The cheap-talk assumption opens the possibility of extending the methods of this paper to prove the existence of equilibrium in more-general extensive-form games with infinite action and information sets.
Keywords: 330